iCan, Empowering Recovery: Evaluating a Patient-Centred Cancer Rehabilitation Programme across the Cancer Care Continuum - Thomas A. Loweth; Suzan R. Taylor; Gareth Mapp; Kim Bebbington; Naomi Atkin; Chris Kite (Diseases)
Background/Objectives: The adverse effects of cancer and the long-term sequelae of associated treatments result in reduced quality of life and increased mortality for patients. Supporting patients with cancer to mitigate adverse outcomes is an important aspect of oncology care and the primary purpose of cancer rehabilitation. A retrospective service evaluation was conducted to evaluate the effectiveness of the core iCan patient-centred cancer rehabilitation service. Methods: At the beginning and end of a five-week programme, a series of questionnaires evaluating changes in mental health and wellbeing, and physical activity performance/attitudes, and functional capacity were administered to participants. Results: Following iCan, we found that functional capacity was improved (30 s sit-to-stand: +6.3 repetition; d = −1.00, p < 0.001) and that self-reported physical activity was increased (~1173 MET-mins/wk; d = −0.76, p < 0.001); participants also perceived greater capability, opportunity, and motivation to be active. Mental wellbeing was also improved (SWEMWBS: d = −0.69, p < 0.001), whilst fatigue was reduced (FACIT: d = −0.77, p < 0.001). Conclusion: It appears that iCan has beneficial effects upon the physical/functional and psychological health of its participants. Where data are available, there appear to be clinically significant improvements across the range of measured functional, wellbeing, and activity/sedentariness outcomes, which suggest that participation in iCan is instrumental in adding value to the health and wellbeing of patients.